Adaptation and Compensation of Vestibular Responses Following Superior Canal Dehiscence Surgery. Issue 9 (October 2016) - Mantokoudis, Georgios; Saber Tehrani, Ali S.; Wong, Aaron L.; Agrawal, Yuri; Wenzel, Angela; Carey, John P.
Abstract : Objective: To describe vestibulo-ocular function and compensatory mechanisms in the immediate postoperative period after superior canal dehiscence surgery. Study Design: Prospective longitudinal study. Setting: Tertiary medical center. Patients: Five patients who underwent plugging of superior semicircular canal via middle cranial fossa approach. Interventions: Bedside quantitative video head impulse testing (vHIT). Main Outcome Measures: Dynamic measures of vestibulo-ocular reflex (VOR) function including VOR gain and compensatory saccades during vHIT. Results: Mean VOR gain of the ipsilateral superior semicircular canal (SC) decreased from 0.71 ± 0.1 preoperatively to 0.28 ± 0.07 on postoperative day (POD) 2–4 ( p  = 0.0031), consistent with plugging. There was also a significant immediate postoperative decrease of VOR gain for the other ipsilateral canals (posterior canal (PC) from gain 0.91 ± 0.33 down to 0.55 ± 0.14, p  = 0.040; horizontal canal (HC) from 0.81 ± 0.08 down to 0.54 ± 0.19, p  = 0.038). On PODs 1–2, compensatory saccades after testing the plugged SC occurred exclusively after the head stopped moving (overt) with latency of 186.2 ms ± 19.9 ms. By POD 7 saccade latency decreased to 141.0 ± 17.5 ms ( p  = 0.032), and saccades were occurring during the vertical head rotation (covert saccades). Follow-up >40 days was consistent with previous findings in that mean SC gain remained low. HC gain recovered fully, but some cases did not have full recovery of PC gain. Conclusion: When the SC is plugged surgically, early quantitative vHIT demonstrates significantly reduced VOR gain for all of the ipsilateral canals. Possible mechanisms include labyrinthine inflammation and loss of perilymph at the time of surgery. Full recovery is typical for the horizontal canal but not always for the PC. Evidence of central compensation occurred by the elicitation of compensatory saccades and by reducing their latencies within the first week after surgery.